Spaces of Contrast. A Spatial Analysis of Franz Grillparzer’s «Der arme Spielmann» (Studia austriaca, 2021)
Physical setting plays an important role in literary writings. After the spatial turn, scholars of literary studies also turned their eyes to the sociological significance of spatial description in literary texts. This essay presents a spatial analysis of Grillparzer’s Der arme Spielmann and argues that in this novella Grillparzer uses the contrast in space as a vital indicator of the disparity between his characters. These spatial contrasts are mainly derived from characters’ differences in terms of birth, class, wealth, education, job and so on. The difficulty of reducing those differences signifies the suffocating political atmosphere in nineteenth-century Austria.